Cohort study of the mortality among patients in New York City with tuberculosis and COVID-19, March 2020 to June 2022 - Alice V. Easton; Marco M Salerno; Lisa Trieu; Erica Humphrey; Fanta Kaba; Michelle Macaraig; Felicia Dworkin; Diana M. Nilsen; Joseph Burzynski (Public Library of Science (PLoS), 2023)
Both tuberculosis (TB) and COVID-19 can affect the respiratory system, and early findings suggest co-occurrence of these infectious diseases can result in elevated mortality. A retrospective cohort of patients who were diagnosed with TB and COVID-19 concurrently (within 120 days) between March 2020 and June 2022 in New York City (NYC) was identified. This cohort was compared with a cohort of patients diagnosed with TB-alone during the same period in terms of demographic information, clinical characteristics, and mortality. Cox proportional hazards regression was used to compare mortality between patient cohorts. One hundred and six patients with concurrent TB/COVID-19 were identified and compared with 902 patients with TB-alone. These two cohorts of patients were largely demographically and clinically similar. However, mortality was higher among patients with concurrent TB/COVID-19 in comparison to patients with TB-alone, even after controlling for age and sex (hazard ratio 2.62, 95% Confidence Interval 1.66-4.13). Nearly one in three (22/70, 31%) patients with concurrent TB/COVID-19 aged 45 and above died during the study period. These results suggest that TB patients with concurrent COVID-19 were at high risk for mortality. It is important that, as a high-risk group, patients with TB are prioritized for resources to quickly diagnose and treat COVID-19, and provided with tools and information to protect themselves from COVID-19.